Roads to renewal : the report of activities and accomplishments of the Civil Works Administration in Michigan, November 1933-March 1934 - Anderson, James R. (Michigan State University Press, 2021)
"This book makes available a little-known Civil Works Administration document that maps the early progress of a crucial initiative in the United States' and Michigan's recovery from the Great Depression. It includes a contextualizing introduction and epilogue by historian James R. Anderson"--